Estratégia empreendedora como mecanismo de ganho de eficiência: estudo de caso numa empresa do setor de termoplásticos - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
This paper deals with analysis of the use of entrepreneurial strategy This paper deals with analysis of the use of entrepreneurial strategy in a company in the thermoplastic industry. To this end, we investigated a company located in the Industrial Pole of Manaus, the Amazon Termotécnica LTDA. Given that, the study focuses on the core aspects of entrepreneurship, as well as the efficiency of the use of an entrepreneurial strategy in an industrial environment, said the following issues: how the entrepreneur's cognitive style associated with the applicability of entrepreneurial strategies can contribute to improvement of performance indicators and the achievement of the objectives of a company in the thermoplastic of the Industrial Pole of Manaus? Thus, the research shows the positive aspects of entrepreneurial strategy, highlighting the characteristics and key elements that contribute to the achievement of goals and objectives. Before elucidating the results, presents a literature review, which presents the main elements on entrepreneurship, explaining the origins of the term, the specification of the currents, and also comes shortly on the absence of a theory that specifies the full complexity of universe entrepreneur. Later, treats the issue of entrepreneurial strategy, and then approaches the leader's role in this context. Highlights the main features, awards, benefits and contrary considerations on the subject. After this review, the results obtained are shown, listing first the general characteristics of the studied company, presenting the strategic scenario and considering the particularities of the universe entrepreneur associated with factors such as turbulence and governing forces competitive environment industry by presenting an assessment on the feasibility the adoption of the use of entrepreneurial strategy in the company object of this study. For analysis and display of results were considered key indicators of performance for the period 2010 and 2011. Thus, they are considered the main strategic trends in the entrepreneurial context, to be followed by that organization in the market which is inserted, emphasizing the dominant strategy compared to the performance indicators obtained. These checks are given the degree of relationship between the interventions of the strategic management of the company studied and its influence on the result, and then present the statements of the impacts from the application of entrepreneurial strategy in our case. With respect to methodology, we opted for the case study method with semiquantitative nature, adopting the kinds of bibliographic research, Field and Documentary. From the results obtained is valid to point out that the analyzes are expressed by means of graphs summarizing the results of the company, establishing a comparison between the period prior to the use of entrepreneurial strategy and the period in which it was applied. In the final considerations are presented reflections and inferences about the intrapreneurial practice in the organization under study, thus concluding that the entrepreneurial strategy may represent the success of organizations, provided that takes elements of the strategies and deliberate craft, joining the entrepreneur's own instincts to knowledge and reality market.
Keywords: Indústria de termoplástico; Polo Industrial de Manaus; Empreendedorismo; Termoplásticos; Estratégia empreendedora; ENGENHARIAS; Estratégia empreendedora; Empreendedorismo; Liderança empreendedora